2005
DOI: 10.1523/jneurosci.3751-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Subunits Effectively Constrain GABAAReceptor Stoichiometry and Recapitulate Receptor Kinetics But Are Insensitive to GABAAReceptor-Associated Protein

Abstract: GABAergic synapses likely contain multiple GABA A receptor subtypes, making postsynaptic currents difficult to dissect. However, even in heterologous expression systems, analysis of receptors composed of ␣, ␤, and ␥ subunits can be confounded by receptors expressed from ␣ and ␤ subunits alone. To produce recombinant GABA A receptors containing fixed subunit stoichiometry, we coexpressed individual subunits with a "tandem" ␣1 subunit linked to a ␤2 subunit. Cotransfection of the ␥2 subunit with ␣␤-tandem subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 55 publications
(62 reference statements)
6
56
0
1
Order By: Relevance
“…Furthermore, the single channel conductance was significantly higher in L929 cells coexpressing ␣1␤2␥2S subunits with GABARAP than without (Everitt et al, 2004), showing high conductance states similar to those observed in native receptors (Fatima-Shad and Barry, 1992;Curmi et al, 1993;Birnir et al, 1994Birnir et al, , 2001. Recently, we and others reported that overexpression of GABARAP increased the cell-surface number of GABA A receptors (Leil et al, 2004;Boileau et al, 2005;Chen et al, 2005). Immunostaining microscopy showed that GABARAP colocalized with intracellular vesicular GABA A receptors and to some extent with plasma membrane GABA A receptors but not with synaptically localized GABA A receptors and gephyrin (Kneussel et al, 2000;Kittler et al, 2001;Leil et al, 2004).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, the single channel conductance was significantly higher in L929 cells coexpressing ␣1␤2␥2S subunits with GABARAP than without (Everitt et al, 2004), showing high conductance states similar to those observed in native receptors (Fatima-Shad and Barry, 1992;Curmi et al, 1993;Birnir et al, 1994Birnir et al, , 2001. Recently, we and others reported that overexpression of GABARAP increased the cell-surface number of GABA A receptors (Leil et al, 2004;Boileau et al, 2005;Chen et al, 2005). Immunostaining microscopy showed that GABARAP colocalized with intracellular vesicular GABA A receptors and to some extent with plasma membrane GABA A receptors but not with synaptically localized GABA A receptors and gephyrin (Kneussel et al, 2000;Kittler et al, 2001;Leil et al, 2004).…”
Section: Introductionsupporting
confidence: 53%
“…GABARAP was shown previously to increase the cell-surface expression of GABA A receptors (Leil et al, 2004;Boileau et al, 2005;Chen et al, 2005). Applying GABARAP IgG from StiffPerson Syndrome patients decreased the surface GABA A receptors in cultured hippocampal neurons (Raju et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, in αβ-expressing receptors, desensitization was more significantly enhanced when F was present in the β subunit. There continues to be some debate regarding the stoichiometry of αβ-expressing receptors [1,2,5,7,11]. Although not definitive, our studies support the presence of 3 β and 2 α subunits in these receptors, since desensitization was more significantly enhanced in α1β2(T6′F) receptors compared to α1(T6′F)β2 receptors.…”
Section: Discussionmentioning
confidence: 42%
“…GABARAP, a 14-kDa polypeptide, originally was identified as an intracellular protein with sequence similarity to light chain 3 of microtubule-associated proteins 1A and 1B (18). GABARAP can interact with the ␥2 subunits of GABA A -Rs (35) and facilitate the surface presentation of GABA A -Rs (2,4).…”
Section: Discussionmentioning
confidence: 99%